MUSLIM CONSUMERS' INTENTION TO SUBSCRIBE TO VIDEO ON DEMAND SERVICES FOR ISLAMIC CONTENT - Muhammad Agung Prayogo; Meri Indri Hapsari (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKEra digitalisasi menjadikan masyarakat mudah untuk melakukan apapun, dimanapun, dan kapanpun termasuk mendapatkan hiburan melalui platform layanan “Video on Demand”. Dalam upaya peningkatan jumlah pengguna berlangganan dalam pasar legal, pelaku penyedia layanan VoD dapat mengoptimalkan peluang pasar yang belum tersentuh yaitu menyediakan konten khusus Muslim berupa tayangan Islami. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi niat konsumen Muslim berlangganan platform VoD guna menikmati tayangan Islami yang tersedia. Kuesioner penelitian disebarkan secara online yang terdiri dari item pengukuran untuk religiusitas (RO), persepsi kualitas konten (PCQ), persepsi kegunaan (PU), persepsi biaya (PC), dan niat berlangganan (ITP). Sebanyak 221 orang mengumpulkan respon dan semuanya sesuai dengan kriteria yang ditentukan. Metode analisis PLS-SEM digunakan untuk menganalisis data yang telah terkumpul. Hasil menunjukkan bahwa RO, PU, PC berpengaruh positif signifikan terhadap Intention to Pay (Subscribe) konsumen Muslim terhadap tayangan Islami yang tersedia di layanan VoD. Sementara itu, PCQ berpengaruh positif tidak signifikan. Penelitian ini diharapkan mampu memberikan gambaran baru mengenai potensi pasar religius di industri media dan hiburan yang masih belum tersentuh. Lebih dari itu, peneliti mengharapkan adanya sinergi dalam penciptaan industri media dan hiburan halal sebagai langkah pengembangan ekosistem halal di Indonesia dan menjadikan Indonesia sebagai pusat Ekonomi Islam di dunia.Kata Kunci: Tayangan Islami, Video on Demand, Religiusitas, Intention to Pay. ABSTRACTThe digitalization era makes people easy to do anything, wherever, whenever including to find entertainment via ”Video on Demand” platforms. In an effort to increase the number of subscribed users in the legal market, vod service providers can optimize the previously untouched market opportunities of providing Muslim special content with Islamic content. The aim of this study is to identify factors affecting Muslim consumers' intent to subscribe to the vod platform to enjoy the available Islamic content. The research questionnaires were spread out online in which there were measuring items to identify religiosity (RO), perceived content quality (PCQ), perceived usefulness (PU), perceived cost (PC), and intention to pay/subscribe (ITP). As many as 221 people have gathered their responses and are all in accordance with the stated criteria. The data collected is analyzed using SEM-PLS. This research finds that religiosity (RO), perceived usefulness (PU), and perceived cost (PC) have a significant positive effect on intention to pay/subscribe (ITP). Meanwhile, perceptions of quality content (PCQ) have a positive effect are insignificant. This research is expected to provide a new picture of the untapped potential of the religious market in the media and entertainment industry. Moreover, the researcher hopes that there will be a synergy in the creation of the halal media and entertainment industry as a step in developing the halal ecosystem in Indonesia and making Indonesia the center of the Islamic economy in the world.Keywords: Islamic content, Video on Demand, Religiosty, Intention to Pay.DAFTAR PUSTAKAAllport, G. W., & Ross, J. M. (1967). Personal religious orientation and prejudice. Journal of Personality  and Social Psychology, 5(4), 432-443.Anto, H. M. B. (2003). Pengantar ekonomi mikro Islami. Yogyakarta: Ekonisia.Bentler, P. M., & Chou, C. P. (1987). Practical issues in structural modeling. Sociological Methods & Research, 16(1), 78–117.Beyah, G., Xu, P., Woo, H., Mohan, K., & Straub, D. (2003). Development of an instrument to study the use of recommendation systems. Proceedings of AMCIS, 269-277.Cheong, H. J., & Park, M. C. (2005). Mobile internet acceptance in Korea. Journal of Internet Research, 15(2), 125-140.Chiang, E., & Assane, D. (2009). Estimating the willingness to pay for digital music. Contemporary Economic Policy, 27(4), 512-522.Davis, F. D., Bagozzi, R. P., & Warshaw, P. R. (1989). User acceptance of computer technology: A comparison of two theoretical models. Management Science, 35(8), 982-1003.Fam, K. S., Waller, D. S., & Erdğoan, B. Z. (2004). The influence of religion on attitudes toward the advertising of controversial products. European Journal of Marketing, 38(5/6), 537-555.Hair, J. F., Sarstedt, M., Ringle, C. M., & Mena, J. A. (2011). An assessment of the use of partial least squares structural equation modeling in marketing research. Journal of the Academy of Marketing Science, 40(3), 414-433.Henley, W. H., Philhours, M., Ranganathan, S. K., & Bush, A. J. (2009), The effects of symbol product relevance and religiosity on consumer perceptions of christian symbols in advertising. Journal of Current Issues and Research in Advertising, 31(1), 89-103.Hirschman, E. C. (1983). Religious affiliation and consumption processes: An initial paradigm. Research in Marketing, 6(1), 131-170.Husted, B. (2000). The impact of national culture on software piracy. Journal of Business Ethics, 26(3), 197-211.Indrawati. (2014). The use of modified unified theory of acceptance and use of technology to predict the behavioural intention toward website. Applied Mechanics and Materials, 568-570, 1586-1592.Jung, Y., Perez-Mira, B., & Wiley-Patton, S. (2009). Consumer adoption of mobile TV: Examining psychological flow and media content. Computers in Human Behavior, 25(1), 123–129.Kalvenes, J., & Neil K. (2008). The Market for Video on Demand. Networks and       Spatial Economics, 8(1). 43-59.La Barbera, P. A., & Gürhan, Z. (1997). The role of materialism, religiosity, and       demographics in subjective well-being. Psychology and Marketing, 14(1), 71-97.Lee, M. (1999). A study on the determinants of service loyalty. Korean Marketing Research, 14(1), 21-45.Lee, B. C., Yoon, J. O., & Lee, I. (2009). Learners' acceptance of e-learning in South Korea: Theories and results. Computers and Education, 53(4), 1320-1329.Liou, D. K., Hsu, L. C., & Chih, W. H. (2015). Understanding broadband television users' continuance intention to use. Industrial Management and Data Systems, 115(2), 210–234.Madnani, D., Fernandes, S., & Madnani, N. (2020). Analysing the impact of COVID-19 on over-the-top media platforms in India. International Journal of Pervasive Computing and Communications, 16(5), 457-475.Minton, E. A. (2015). In advertising we trust: Religiosity’s influence on marketplace and relational trust. Journal of Advertising, 44(4), 403-414.Muflih, M. (2006). Perilaku konsumen dalam perspektif ilmu ekonomi Islam. Jakarta: Raja Grafindo Persada.Muhamad, N., & Mizerski, D. (2010). The constructs mediating religions’ influence on buyers and consumers. Journal of Islamic Marketing, 1(2), 124-135.Park, S., Kang, S. U., & Zo, H. (2016). Analysis of influencing factors on the IPTV    subscription: Focused on the moderation role of user perceived video quality. Information Technology & People, 29(2), 419-443.Petersen, L. R., & Roy, A. (1985). Religiosity, anxiety, and meaning and purpose: Religion’s consequences for psychological well-being. Review of Religious Research, 27(1), 49-62.Shah Alam, S., Mohd, R., & Hisham, B. (2011). Is religiosity an important determinant on Muslim consumer behaviour in Malaysia?. Journal of Islamic Marketing, 2(1), 83-96.Shin, D. H. (2009). Determinants of customer acceptance of multi-service network: An implication for IP-based technologies. Information & Management, 46(1), 16-22.Taylor, V. A., Halstead, D., & Haynes, P. J. (2010). Consumer responses to Christian religious symbols in advertising. Journal of Advertising, 39(2), 79-92.Tsu W. T., Marthandan, G., Yee, L. C., A., Ooi, K., & Arumugam, S. (2009). What drives Malaysian m‐commerce adoption? An empirical analysis. Industrial Management & Data Systems, 109(3), 370–388.Tuan, N. M. (2012). Effects of service quality and price fairness on student satisfaction. International Journal of Business and Social Science,  3(9), 132-150.Ustaahmetoğlu, E. (2020). The influence of different advertisement messages and levels of religiosity on attitude and purchase intention. International     Journal of Islamic and Middle Eastern Finance and Management, 13(2), 339-356.Weinberger-litman, S. L., Rabin, L. A., & Fogel, J. (2016). Body Dissatisfaction and Disordered Eating among Jewish Women: The Role of Religious Orientation and Spiritual Well-Being (Yael Latze). Springer International Publishing. Retrieved from https://doi.org/10.1007/978-3-319-32742-6Weniger, S. (2010). User adoption of IPTV: A research model. Bled Proceedings. Ljubljana: Slovenia.Zeithaml, V. A. (1988). Consumer perception of price, quality, and value: A meansend model and synthesis of evidence. Journal of Marketing, 52(3), 2-22.